2021
DOI: 10.1111/medu.14534
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of students access to resources in an examination

Abstract: Introduction: Assessment of healthcare professionals should be authentic to clinical practice. As clinicians regularly use resources in practice, similar resources should be available to those sitting assessment. There is limited information on the impacts of open-book (resource) assessments on standard setting for use in high-stakes assessments. This research aims to explore the effects on standard setting and student perceptions when open vs closed resources are available in high-stakes assessment of medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The low mean percent score of the students in this study could be possibly due to the lack of experience in-terms of preparation, effective utilization and attempt of OBE by the students. However, studies have reported low scores, high scores, or no difference in scores of students in OBE when compared to the closed book exam (CBE) in literature [ 9 , 12 , 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low mean percent score of the students in this study could be possibly due to the lack of experience in-terms of preparation, effective utilization and attempt of OBE by the students. However, studies have reported low scores, high scores, or no difference in scores of students in OBE when compared to the closed book exam (CBE) in literature [ 9 , 12 , 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%